ANALISIS WAKTU BAKU PROSES PRODUKSI ROTI DENGAN METODE STOPWATCH DI UKM FANDRA BAKERY - Mufrida Meri; Hary Fandeli; Ratih Zulia Ramadhani (Smart Education, 2022)
Indonesia has many industries engaged in food and culinary. Among them are small and medium enterprises (SMEs) which are very large and make a large contribution to Indonesian economy. To ensure the sustainability of the industry, there is a standard time for each production process. Standard time is the work of observing and recording the working times of both each element or cycle using the tools that have been provided. UKM Fandra Bakrie is one of the small and medium-sized industries that produce bread in Padang City. It is important to know the standard time of the bread making process so that it becomes a reference for management policies. Time measurement using the stopwatch method by calculating the cycle time of each element of bread making work. Measurement data is tested statistically using uniformity tests and data adequacy tests. Then the calculation of standard time by considering adjustment factors and leeway factors. Standard time is used as the basis in determining the amount of production in a given period and for planning production. Based on the results of the study obtained the total time standard for bread production at UKM Fandra Bakery is 287.99 seconds / unit or 4.8 minutes / unit. Thus UKM Fandra Bakery is able to produce as much as 3,200 Pcs per day.